INDONESIA'S CHAIRMANSHIP OF ASEAN 2023: ADVANCING REGIONAL COLLABORATION ON ENVIRONMENTAL DIPLOMACY - Listianto, Karunya Saka (Jurnal Studi Diplomasi dan Keamanan, 2025)
Indonesia, as the chair of ASEAN in 2023, focused on promoting ASEAN as a fast-growing, inclusive, and sustainable economic region with the theme "Epicentrum of Growth". To achieve the goal, ASEAN emphasized the need for a strong regional health framework, food and energy security, and financial stability. However, it is important to mention that the theme did not specifically address environmentalissues, despite Indonesia's efforts to lead initiatives addressing environmental concerns in Southeast Asia during its time as ASEAN chair. The purpose of this paper was to examine Indonesia's role in environmental diplomacy while serving as the ASEAN chair in 2023. This diplomacy involved promoting joint actions to address climate change, preserve biodiversity, and promote sustainable resourcemanagement. Indonesia effectively involved ASEAN member countries in coordinated environmental efforts through hosting crucial meetings, workshops, and collaborative projects in the forms of collaborative agreements and initiatives during its chairmanship. The study employs a single case study methodology, wherein data collected from relevant documentation concerning Indonesia's involvemen